The analysis of dyadic deaths - Zummerova, Anezka; Sidlo, Jozef; Kuruc, Roman; Valent, Denis; Kovac, Peter; Zdarílek, Martin (Soudni lekarstvi, 2015)
In the work we analyze three cases of unusual dyadic deaths when the perpetrator of homicide committed suicide shortly after the murder. In the first case a man stabbed his girlfriend with a knife and subsequently committed a car crash suicide. In the second case an apparent simultaneous hanging of a married couple turned out to be homicide-suicide act. In the last case a man shot his ex-wife while she was on a walk with their dog and in a short time turned the gun against himself.
Keywords: dyadic death - homicide - suicide.; Homicide; soudní lékařství; mužské pohlaví; ženské pohlaví; Forensic Medicine; Suicide; dospělí; Humans; sebevražda; Adult; Female; vražda; lidé; Male